An Analysis of Speech Acts in the Movie Avengers: Endgame - Windriani, Dian; Ainiyaya, Siti; Istiara, Febriyantina; Zulianti, Hajjah (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2026)
This study aims to identify the types of illocutionary speech acts and determine the most dominant type used in the movie Avengers: Endgame. This research employed a descriptive qualitative method using Searle’s theory of speech acts as the analytical framework. The primary data consisted of dialogues spoken by selected characters, namely Tony Stark, Steve Rogers, Thanos, and Scott Lang. Data were collected through observation and note-taking techniques, followed by classification and analysis using content analysis procedures. The findings revealed that five types of illocutionary acts were present in the movie: declarative, assertive, expressive, directive, and commissive. A total of 64 utterances were identified, consisting of 4 declaratives (6%), 16 assertives (25%), 7 expressives (11%), 34 directives (53%), and 3 commissives (5%). Among these, directives were found to be the most dominant type. This dominance indicates that the characters frequently use language to give commands, make requests, and direct actions, reflecting power relations and strategic interactions within the storyline. The findings contribute to a better understanding of how speech acts function in cinematic discourse and highlight the importance of pragmatic competence in interpreting meaning in context.